Characterization of the radiosynthesis and purification of [18F]THK-5351, a PET ligand for neurofibrillary tau. (December 2017) - Betthauser, Tobey J.; Ellison, Paul A.; Murali, Dhanabalan; Lao, Patrick J.; Barnhart, Todd E.; Furumoto, Shozo; Okamura, Nobuyuki; Johnson, Sterling C.; Engle, Jonathan W.; Nickles, Robert J.; Christian, Bradley T.
Abstract: This work characterizes the radiochemical synthesis, purification, and formulation of [ 18 F]THK-5351, a tau PET radioligand, and develops an automated radiosynthesis routine (ELIXYS, Sofie Biosciences). Nucleophilic radiofluorination reaction was complete by 7 min at 110 °C with radiochemical yields proportional to precursor mass (0.1–0.5 mg). Optimized HPLC purification produced radiotracer product with no chemical impurities observed on analytical HPLC in formulation. Automated radiosynthesis (ELIXYS), HPLC purification and formulation was completed in 86 min producing formulated product suitable for human research use. Highlights: Characterization of [ 18 F]THK-5351 radiosynthesis with varying precursor mass. Optimization of pre-HPLC and HPLC purification. Automated radiosynthesis of [ 18 F]THK-5351 using the Sofie ELIXYS. Formulation instability of [ 18 F]THK-5351 under inert head gas.